MENGIDENTIFIKASI KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS TIPE 2 DI BERBAGAI PUSKESMAS DI INDONESIA - Efadri, Yoky; Sutjiatmo, Afifah B. (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Diabetes mellitus is a chronic disease that sufferers suffer from throughout their lives and is a global problem. Non-compliance in taking medication in diabetes mellitus patients worsens the quality of life of patients. This article aims to identify the level of medication compliance in patients with diabetes mellitus. The method used in this article is a narrative literature review through a search of the PubMed, Google Scholar, and ScienceDirect. By identifying related articles, 1258 articles were obtained. Filtered based on inclusion criteria and 20 articles met the criteria. The results of the study showed low compliance in taking medication in patients with diabetes mellitus. Based on the article search, the lowest level of medication compliance was 94.4%. To improve compliance in taking medication in patients with diabetes mellitus, an important role of pharmacists is needed to intervene, monitor, and also increase knowledge of patients with diabetes mellitus in order to achieve stable glucose levels.